1991
DOI: 10.2172/6347484
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of asphaltene and wax precipitation

Abstract: Organic deposition has been shown to be a major problem associated with oil recovery by gas flooding. Industry is lookingfor ways of controllingorganicdepositionand economicmethods that can remedy the problem. A predictivetechniqueis crucialto the solutionof this problem, and this research projectwas designed to focus on the developmentof a predictivetechnique. A thermodynamicmodel has been developed to describe the effects of temperature, pressure,and compositionon asphaltene precipitation. The model employes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 1 publication
2
46
0
Order By: Relevance
“…Chung et al (1991) published results which showed that a quarter of the asphaltenes flocculated with n-pentane were redissolved. Kokal et al (1992) show that with two Canadian oils, the precipitates formed could be redissolved by adding heavy oil.…”
Section: Flocculation Reversibility?mentioning
confidence: 99%
“…Chung et al (1991) published results which showed that a quarter of the asphaltenes flocculated with n-pentane were redissolved. Kokal et al (1992) show that with two Canadian oils, the precipitates formed could be redissolved by adding heavy oil.…”
Section: Flocculation Reversibility?mentioning
confidence: 99%
“…Components which contain the large amount of N, S, and O atoms are known as asphaltene [1,2]. They have high molecular weight and complex combination with cyclic structures and paraffin chain which is connected to the NSO atoms [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Hirschberg et al (1984) and Chung et al (1991) reported a series of titration experiments in tank-oil samples with liquid alkanes from n-pentane to n-hexadecane as diluents, to determine the precipitation onset composition, the amount of material precipitated, and the solubility properties of asphaltenes. Kokal et al (1992) reported the amount of asphaltenes precipitated when two Canadian heavy oils with a high content of asphaltenes were titrated with various n-alkanes (n-pentane to n-decane) at different dilution ratios.…”
Section: Introductionmentioning
confidence: 99%